Thrombolytic therapy for patients with acute ischemic stroke: systematic review and network meta-analysis of randomized trials - Sun, Li-Chao-Yue; Li, Wen-Shu; Chen, Wei; Ren, Zhao; Li, Chun-Xing; Jiang, Ze; Wang, Le; Wang, De-Li; Xie, Qing (Frontiers in Neurology, 2025)
ObjectiveTo systematically compare the benefits and risks of all thrombolytic agents (tenecteplase, reteplase, and alteplase) at different doses for thrombolytic therapy in patients with acute ischemic stroke (AIS).BackgroundAlteplase is the cornerstone treatment for AIS, but alternative thrombolytic agents are needed. The efficacy and safety of tenecteplase and reteplase, compared to alteplase, remain unclear, as does the optimal dosing for these treatments.MethodA systematic search was conducted in PubMed, Web of Science, SCOPUS, and the Cochrane Central Register of Controlled Trials (CENTRAL) for relevant English-language studies up to July 5, 2024. Randomized controlled trials (RCTs) comparing standard-dose alteplase with varying doses of tenecteplase or reteplase in AIS patients were included. Primary outcomes were functional outcome at 90 days, symptomatic intracranial hemorrhage, death within 90 days, and serious adverse events. Data on study characteristics, patient demographics, interventions, and outcomes were extracted, and bias risk assessed. A multivariate random-effects model was used for network meta-analysis to derive odds ratios (OR) and 95% confidence intervals (CI).ResultTwelve RCTs were included (10 with tenecteplase, 2 with reteplase) involving 6,633 patients, all compared against 0.9 mg/kg alteplase. In comparison with alteplase, tenecteplase demonstrated OR of 1.08 for achieving an excellent functional outcome at 90 days (95% CI: 0.97 to 1.22, P = 0.17). Reteplase, on the other hand, showed a significantly higher OR of 1.55 for the same outcome (95% CI: 1.23 to 1.95, P = 0.0002). Reteplase at 18 mg + 18 mg (OR 1.6, 95% CI: 0.91–2.5) showed a higher probability of achieving an excellent functional outcome at 90 days compared to alteplase. When considering a good functional outcome at 90 days, tenecteplase had an OR of 1.03 (95% CI: 0.81 to 1.3, P = 0.82), while reteplase had an OR of 1.15 (95% CI: 0.61 to 2.19, P = 0.66). Tenecteplase at 0.25 mg/kg (OR 1.3, 95% CI: 0.79–2.5) had the highest probability of achieving a good functional outcome at 90 days. For safety outcomes, 0.25 mg/kg tenecteplase had lower incidences of symptomatic intracranial hemorrhage (OR 0.88, 95% CI: 0.35–1.8), death within 90 days (OR 0.91, 95% CI: 0.54–1.4), and serious adverse events (OR 1.0, 95% CI: 0.47–2.3) compared to alteplase, though differences were not statistically significant. Reteplase at 18 mg + 18 mg had higher incidences of death within 90 days (OR 1.2, 95% CI: 0.48–3) and serious adverse events (OR 1.4, 95% CI: 0.4–5.0) compared to alteplase, without significant differences. Subgroup analysis showed better efficacy with 0.25 mg/kg tenecteplase in Asians (OR 1.18, 95% CI 0.96–1.45, P = 0.12) than in Caucasians (OR 1.08, 95% CI 0.9–1.3, P = 0.39).ConclusionThis study suggests that tenecteplase and reteplase are viable alternatives to alteplase for thrombolysis in AIS. Tenecteplase at 0.25 mg/kg and reteplase at 18 mg + 18 mg may offer better efficacy compared to standard-dose alteplase, although the risk of adverse events with reteplase should be considered. Tenecteplase at 0.25 mg/kg appears to provide the best benefit-risk profile based on current evidence. Further head-to-head trials of tenecteplase and reteplase are needed to determine the optimal thrombolytic agent and dosing.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, PROSPERO CRD42024566146.